Association of Retinopathy with Chronic Kidney Disease in Diabetes Mellitus (BIRDEM Medical Journal, 2018)
Background: Diabetic retinopathy (DR) and nephropathy are two major complications of diabetes mellitus carrying significant morbidity and mortality. In this study DR was investigated in different stages of chronic kidney disease (CKD) to find out possible association of these two devastating complications.Methods: This cross-sectional study was conducted in 150 diabetic patients having CKD in BIRDEM. CKD was defined as estimated glomerular filtration rate (eGFR) of 30 mg/day in at least two occasions in 3 months apart. Retinopathy was assessed by direct fundoscopic examination and confirmed by color fundus photography. Severe DR (SDR) included proliferative diabetic retinopathy, severe non-proliferative DR and maculopathy; whereas microaneurysm regarded as non-severe retinopathy.Results: Majority (68%) of the respondents had some form of retinopathy (38.35% SDR and 29.65% nonsevere). There was strong association between different levels of albuminuria (UAER) and DR (p